Pengaruh Kualitas Audit dan Tata Kelola Perusahaan terhadap Manajemen Laba pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Kennardi Tanujaya; Verent Verent (Faculty of Economics, Universitas Internasional Batam, 2020)
This study is aimed to analyze audit quality and corporate governance towards earning management. The independent variables used in this study are auditor size, specialist audit, tenure audit, ownership concentration, internal ownership, family ownership, institutional ownership, the board size, independent directors, and board activity. Meanwhile, leverage, company size, and operational cash flow are used as control variables in this study. Earning management is the dependent variable measured using discretionary accruals. This study has a sample of 360 companies listed on the Indonesia Stock Exchange within the 2014-2018 periods. Samples are analyzed using a purposive sampling method and there are 1,672 observational data examined in this study. Data are tested by applying the panel regression method. The research concluded that independent variables which include specialist audits, ownership concentration, internal ownership, and institutional ownership do not significantly influence profit management. While results of the independent variables which include auditor size, audit tenure, family ownership, the board size, independent directors, and board activity are variables that have a significant positive relationship. Control variables that include leverage, company size, and operating cash flow have a significant effect on earning management that opposed the independent variable, which is significantly negative.